Celebrating Scott Williams Birthday at Fresno-Merced Counties Legal Services - Watkins, Howard::::::::: (1980)
Eddie Mae Lomack, Janice Pearson, ?, Ray Starks, ???? Standing Janice Pearson holding 35 mm camera